Twelve days of Christmas [large type] : a novel - Macomber, Debbie (Random House Large Print, 2016)
Friendly and bubbly, Julia Padden likes nearly everyone, but her standoffish neighbor, Cain Maddox, presents a particular challenge. No matter how hard she's tried to be nice, Cain rudely rebuffs her at every turn. But when Julia catches Cain stealing her newspaper from the lobby of their apartment building, that's the last straw. She's going to break through Cain's Scrooge-like exterior by killing him with kindness. To track her progress, Julia starts a blog called The Twelve Days of Christmas. Little by little Julia chips away at Cain's gruff façade to reveal the caring man underneath, and unbelievably, she feels herself falling for Cain--and she suspects that he may be falling for her as well. But as the popularity of her blog continues to grow, Julia must decide if telling Cain the truth about having chronicled their relationship to the rest of the world is worth risking their chance at love.